DLSU faculty elected president of the Philippine Economic Society - De La Salle University, Manila (Animo Repository, 2009)
Dr. Winfred Villamil, associate professor of the Economics Department, was elected president of the Philippine Economic Society (PES) during the meeting of the incoming Board of Directors. The PES is the largest professional organization of economists in the country and is well known in the international community of professional economic associations. Through its conferences and symposia, it provides a venue for the open and free discussion of a wide range of policy issues. With its publication, The Philippine Review of Economics, the society also performs a major role in raising the standard of economic research in the country.